The Level of Social Vulnerability for Flood Disaster in the City of Tangerang, Banten Province. - Tri Desti Handayani; Muzani; Ilham B. Mataburu (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2021)
This study aims to determine the level of social vulnerability to flood disaster in the city of Tangerang by using the SoVI (Social Vulnerability Index) method. This study uses 6 indicators to assess the level of social vulnerability for flood disasters in the sub district unit. Each sub district unit is calculated quantitatively using the PCA technique (Principal Component Analysis) and weighting is carried out on each indicator. Each weight describes the relationship between each indicator / variable and its level of vulnerability. The results of this study indicate that there are 5 categories of vulnerability levels. The very low category of social vulnerability is found in 4 sub district, namely: Pasar Baru, Nambo Jaya, Panunggangan Timur, and Sukarasa. The low category is found in 16 sub district including: Kunciran Jaya, Pakojan, and Kelapa Indah. There are moderate categories in 27 sub district including Nerogtog, Cipete, and Babakan. The high category is in 15 sub district including Gebang Raya, Kunciran, and Piang. There are very high categories in 7 sub district including: Kunciran Indah, Petir, and Cipondoh Indah.